A Study of the Impact of Written Premiums and Paid Claims on the Financial Solvency of Insurance Companies in the Kingdom of Saudi Arabia (The International Journal for Scientific Research, 2023)
The aim of this study is to discover the relationship between written premiums and paid claims as two independent variables and the required solvency as a dependent variable for a sample of insurance companies in the Kingdom of Saudi Arabia. To achieve this, in this research, we calculated the solvency required to be achieved by the insurance company according to the method of written premiums, which are found in the insurance companies’ control list issued by the Saudi Central Bank, and relied on the financial reports issued and published for five companies, which represent a sample of the Saudi insurance market during the study period from 2012 to 2021, these companies were chosen due to the availability of the necessary data to complete this study within the required period of ten years. The Statistical Package for Social Sciences (SPSS) was used to test the research hypothesis, and the results of hypothesis testing showed that the written premiums affect positively and significantly the required solvency for all the researched insurance companies. The results also showed that the paid claims affect positively and significantly the solvency required for these companies. According to the results obtained, the higher the written premiums, the higher the solvency demanded by the insurance companies, which will have a significant impact on maintaining the solvency of the company, fulfilling its obligations in the long term, and reducing the level of risks facing the company's assets, and the increase in the volume of claims leads to an increase in the prices of insurance products. This leads to an increase in the volume of written premiums and, thus, an increase in the required solvency margin. Therefore, this study recommends the necessity of commitment and striving to achieve the required solvency margin or higher by increasing the volume of subscriptions due to their significant contribution to the insurance company being financially full. The company's financial efficiency, and we also recommend the need to choose low-cost risks to reduce the volume of claims and reduce the price of insurance premiums to attract the largest possible number of subscribers and thus increase the volume of written premiums.
Keywords: Solvency; Written Premiums; Paid Claims; Insurance; Statistical Analysis